2012
DOI: 10.7314/apjcp.2012.13.11.5857
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Glioma Incidence and Laterality Correlates with Use of Mobile Phones - a Nationwide Population Based Study in Israel

Abstract: Introduction: Mobile phones are in extensive use worldwide and concerns regarding their role in tumor formation were raised. Over the years multiple studies were published in order to investigate this issue using several approaches. The current study looks at secular trends of brain gliomas (low and high grade) incidence and changes in tumor's laterality over 30 years in a population extensively using this technology with a possible correlation to the spread of use of mobile phones. Materials and Methods: All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…Thus, latterly gliomas seem to occur more frequently in older ages. Specifically a significance increase of high grade glioma was described (Barchana et al, 2012). Similarly, American study assessment described an increase of incidence rate with the 4th power of age in glioblastoma subtype (Dubrow and Darefsky, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, latterly gliomas seem to occur more frequently in older ages. Specifically a significance increase of high grade glioma was described (Barchana et al, 2012). Similarly, American study assessment described an increase of incidence rate with the 4th power of age in glioblastoma subtype (Dubrow and Darefsky, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With increase in the use of mobile phones, an area of interest for epidemiological research on brain tumors is the possible association of radio frequency (RF) radiation ie, radiation emitted by mobile phones. However, the results on cellular effects of RF radiation do not hold much of biological plausibility and were not convincing for association of RF radiation (Barchana et al, 2012). Jazayeri et al (2013) has shown that cancer registries should also include benign brain tumors for a better understanding of the epidemiology of brain tumors as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Relative risks were below 1 for meningiomas and gliomas, and the risk of acoustic neuroma was slightly elevated and not statistically significant (Berg et al, 2006). While a shift in laterality towards left-sided tumors,for both low and high-grade gliomas, has been proposed as evidence for a link (Barchana et al, 2012), there is no plausible reason why the massively increased use of wireless phones has not affected the relatively stable incidence time trends for brain tumours among children and adolescents in Nordic countries (Aydin et al, 2012) and the US data (Little et al, 2012). A study of the risk of brain tumors among workers of various specialties who could be exposed to low frequency electromagnetic field was also inconclusive (Kleinerman et al, 2005).…”
Section: Discussionmentioning
confidence: 97%